TOTAL PERFECT DOMINATION OF AN INTERVAL-VALUED FUZZY GRAPHS - AL-Ahmadi, Faisal M.; Shubatah, Mahiuob M. Q.; Hasan, Yahya Q. (IJRDO -JOURNAL OF MATHEMATICS, 2022)
A perfect dominating set Dp of an interval-valued fuzzy graph G = (A, B) of G∗ = (V, E) is called a total perfect dominating set of G if every vertex of G is domi- nates to at least one vertex of Dp and denoted by Dtp. In This article, the new kind of parameter total perfect domination in interval-valued fuzzy graphs is defined and stud- ied. We research and concludes Some bounds on total perfect domination number γtp(G) and Γtp(G) for several classes in interval-valued fuzzy graphs and obtained. Finally we introduce characteristics between the total perfect domination and perfect domination, total domination and connected in interval-valued fuzzy graphs.